2013
DOI: 10.1371/journal.pone.0066825
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma Virus Infection Promotes NK Lysis of Malignant Gliomas In Vitro and In Vivo

Abstract: Myxoma virus (MYXV) is a well-established oncolytic agent against different types of tumors. MYXV is also known for its immunomodulatory properties in down-regulating major histocompatibility complex (MHC) I surface expression (via the M153R gene product, a viral E3-ubiquitin ligase) and suppressing T cell killing of infected target cells. MHC I down-regulation, however, favors NK cell activation. Brain tumors including gliomas are characterized by high MHC I expression with impaired NK activity. We thus hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 33 publications
0
44
0
1
Order By: Relevance
“…It is not yet clear if MYXV is capable of generating an adaptive immunotherapeutic response in gliomas, however it has been shown in other cancer models 31 as well as to enhance adoptive NK immunotherapy. 17 Additional investigation probing the nature of the glioma microenvironment before and after virotherapy, as well as the specific mechanisms by which the innate immune response limits MYXV infection rates, could lead to a more targeted approach to enhance viral infection while initiating anti-tumour immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not yet clear if MYXV is capable of generating an adaptive immunotherapeutic response in gliomas, however it has been shown in other cancer models 31 as well as to enhance adoptive NK immunotherapy. 17 Additional investigation probing the nature of the glioma microenvironment before and after virotherapy, as well as the specific mechanisms by which the innate immune response limits MYXV infection rates, could lead to a more targeted approach to enhance viral infection while initiating anti-tumour immunity.…”
Section: Discussionmentioning
confidence: 99%
“…11, 15-17 Animals were followed until they lost ≥20% of body weight or had trouble ambulating, feeding, or grooming. Intracranial injection of vMyx-FLuc or vMyx-GFP was performed on day 14 for all lines in survival or bioluminescent studies, and on day 12 for flow cytometric studies.…”
Section: Methodsmentioning
confidence: 99%
“…Между тем, грануло-опосредованная цитотоксичность может иметь большое значение в противоопухолевом имму-нитете при глиальных опухолях головного моз-га, поскольку многие глиомные опухолевые ли-нии резистентны к рецептор-опосредованному апоптозу [6,8]. В литературе имеются отдельные сообщения о чувствительности клеток глиобла-стомы к перфорин/гранзим Б-опосредованному лизису [11,21]. Исследования in situ показали, что в области иммунологического синапса меж-ду глиобластомными клетками человека и опу-холь-инфильтрирующими CD8 + Т-лимфоцитами обнаруживается гранзим Б [5].…”
Section: Discussionunclassified
“…The virus downregulates class I major histocompatibility complex (MHC) expression on the surface of infected cells (103); a recent study demonstrated this effect in infected glioma cells in vivo (104). This downregulation led to increased natural killer (NK) cell–mediated recognition and efficient killing of infected glioma cells (104). Thus, MYXV infection not only leads to the direct killing of cancer cells but also promotes early immune cell–mediated antitumor responses.…”
Section: Myxoma Virus Oncolytic Virotherapymentioning
confidence: 99%